Detergent-resistant plasma membrane proteome to elucidate microdomain functions in plant cells - Takahashi, Daisuke; Kawamura, Yukio; Uemura, Matsuo (Frontiers in Plant Science, 2013)
Although proteins and lipids have been assumed to be distributed homogeneously in the plasma membrane (PM), recent studies suggest that the PM is in fact non-uniform structure that includes a number of lateral domains enriched in specific components (i.e., sterols, sphingolipids, and some kind of proteins). These domains are called as microdomains and considered to be the platform of biochemical reaction center for various physiological processes. Microdomain is able to be extracted as detergent-resistant membrane (DRM) fractions, and DRM fractions isolated from some plant species have been used for proteome and other biochemical characterizations to understand microdomain functions. Profiling of sterol-dependent proteins using a putative microdomain-disrupting agent suggests specific lipid–protein interactions in the microdomain. Furthermore, DRM proteomes dynamically respond to biotic and abiotic stresses in some plant species. Taken together, these results suggest that DRM proteomic studies provide us important information to understand physiological functions of microdomains that are critical to prosecute plant’s life cycle successfully in the aspect of development and stress responses.